Cultural, biological and chemical control of the white rot fungus (Sclerotium cepivorum, Berk) in onions (Allium cepa) in Arequipa´s countryside - Gonzales, M. (2018)
This experiment was carried out at the province of Arequipa, to determine broccoli residual effects on the sclerotia population of Sclerotium cepivorum on the soil and determine the best fungicides and biocontrol agents on the biggest red onion production. In two field areas infected with Sclerotium cepivorum, soil samples were carried out to determine the number of sclerotia at the beginning and the end of the trial. One area received broccoli residues before treatment installation. The experiment had a laboratory and a field phase. The block design was used completely randomized (DBCA), using seven fungicide treatments (T1) control, Iprodione (T2), Thiabendazole (T3), Boscalid (T4), Carbendazim (T5), T harzianum (T6), Bacillus subtilis (T7). Both areas received the same treatments. The density of sclerotia in the soil was not significant between these areas. However, the addition of broccoli had lower percentages of incidence and severity and higher yields in all treatments. At the area that received broccoli, the Boscalid (T4) and the Iprodine (T2) fungicide were highlighted with 43.33 T/ha and 28.33 T/ha, respectively; the area without broccoli, the T4 with 38.33 T/ha and T2 with 25.56 T/ha. T5 (Carbendazim) had the lowest yield: 15.00 T/ha without broccoli and 19.58 T/ha with broccoli.